2019
DOI: 10.1017/s136898001900257x
|View full text |Cite
|
Sign up to set email alerts
|

Can methods based on spot urine samples be used to estimate average population 24 h sodium excretion? Results from the Isfahan Salt Study

Abstract: Objective:To assess agreement between established methods of estimating salt intake from spot urine collections and 24 h urinary Na (24hUNa) and then to develop a valid formula that can be used in the Iranian population to estimate salt intake from spot urine samples.Design:A validation study. Three spot urine samples were collected (fasting second-void morning; afternoon; evening) on the same day as a 24 h urine collection. We estimated 24hUNa from spot specimens using the Kawasaki, Tanaka and INTERSALT equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…He and colleagues report further evidence that estimates of sodium intake from methods based on spot urine samples are inaccurate and biased by systematic error, 23 which is consistent with previous findings in diverse populations 56‐60 . Furthermore, for the first time, He et al 23 provide novel data suggesting that the use of the Kawasaki equation, a spot urine‐based estimate, changes the linearity of the sodium‐mortality association.…”
Section: Discussionmentioning
confidence: 54%
“…He and colleagues report further evidence that estimates of sodium intake from methods based on spot urine samples are inaccurate and biased by systematic error, 23 which is consistent with previous findings in diverse populations 56‐60 . Furthermore, for the first time, He et al 23 provide novel data suggesting that the use of the Kawasaki equation, a spot urine‐based estimate, changes the linearity of the sodium‐mortality association.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have more recently reported results using the Kawasaki, Tanaka, INTERSALT, and other spot urine algorithms in a variety of populations. In an Iranian study of 79 adults, Mohammadifard et al ( 33 ) reported that the Tanaka algorithm Na estimate was not significantly different from the study 24-h urine Na, although 2 newly proposed algorithms including self-assessment of discretionary salt and participant characteristics of BMI, sex, age, and physical activity were less biased than the Tanaka algorithm. Two large studies, one in France ( 34 ) and one in the Shandong province of China ( 35 ), ruled out the Kawasaki, Tanaka, and INTERSALT algorithms for estimating individual Na intake, while not ruling out their use for group estimation.…”
Section: Discussionmentioning
confidence: 97%
“…Spot urine collection is an easily applicable alternative in estimating dietary Na intake. Increasing studies aim to reveal the most accurate formula for converting spot Na to 24UNa, comparing not only those commonly used (17,(44)(45)(46)(47)(48) but also those newly designed (49,50) against the gold-standard 24UCol. The mostly studied formulas are the INTERSALT equation, the Tanaka equation and the Kawasaki equation.…”
Section: Discussionmentioning
confidence: 99%
“…The mostly studied formulas are the INTERSALT equation, the Tanaka equation and the Kawasaki equation. Despite some controversies (50) , a large number of studies support that among the existing equations, the INTERSALT performs better in estimating the 24UNa showing the least bias (44,45,49,51,52) . In our findings, the INTERSALT equation presented the lowest bias among all the other equations; however, it was moderately correlated with 24UNa and also presented consistent bias in Bland-Altman plots by underestimating Na intake at low levels of Na excretion and overestimating at high levels of Na excretion.…”
Section: Discussionmentioning
confidence: 99%